2000
DOI: 10.1364/ol.25.000646
|View full text |Cite
|
Sign up to set email alerts
|

15-µm emissions from laser-diode-pumped Nd-doped microchip solid-state lasers

Abstract: 1.5-mum emissions from Nd:YAG, Nd:YVO(4), and LiNdP(4) O>(12) microchip lasers pumped by laser diodes have been observed. These coherent emissions are attributed to the effect of high-energy modified lattice vibration owing to the existence of Nd ions as well as to stimulated intracavity Raman scattering enhanced by the microchip configuration. A four-wave mixing process involving two lasing fields and a Stokes field was identified as the generator of new adjacent 1.5-mu;m emission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…2 and described in Ref. 4. How different are the response characteristics of the Stokes-like emission from the probe beam and those of the emission generated from the four-wave mixing?…”
Section: Pump-probe Experiments With Infrared Emissions a Experimentmentioning
confidence: 99%
See 2 more Smart Citations
“…2 and described in Ref. 4. How different are the response characteristics of the Stokes-like emission from the probe beam and those of the emission generated from the four-wave mixing?…”
Section: Pump-probe Experiments With Infrared Emissions a Experimentmentioning
confidence: 99%
“…1 Self-Raman-shifting pulsing, in which the Raman crystal is also the host material for the rare-earth ions that are active in lasing, has been reported in Nd:KGd(WO 4 ) 2 lasers. 2,3 Recently Hwong et al observed coherent 1.5-m laser emissions from laser-diode-(LD-) pumped microchip Nd-doped solid-state lasers, such as Nd:YAG, Nd:YVO 4 , and LiNdP 4 O 12 (LNP), 4 although there is no such optical transition in Nd atoms. These emissions possess energies that are lower by ϳ3000 cm Ϫ1 than the fundamental emissions near 1 m. In the case of LNP, three emissions whose wavelengths are separated by different energies from the fundamental lasing wavelengths at 1048, 1055, and 1060 nm, which operate on a double ⌳ scheme and form mirror images, were observed in this experiment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…%-doped sample, which is a similar behavior to LD-pumped microchip Nd:YAG single crystalline lasers. 8) While, in the 5 at. %-doped sample, the 1061-nm-transition oscillation was not observed.…”
mentioning
confidence: 96%